2021
DOI: 10.1093/ibd/izab300
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Inflammatory Bowel Disease and Dementia: A Longitudinal Cohort Study

Abstract: Background The association between inflammatory bowel disease (IBD) and dementia remains uncertain. We aim to investigate whether IBD is associated with higher dementia risk. Methods Using multivariable Cox regression models, we analyzed the onset of all-cause dementia among 497,775 participants, including 5778 IBD patients in the UK Biobank as primary analysis. In secondary analysis, we further examined the difference in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…22,23 Contrasting these studies, a Swiss cross-sectional study found an approximately 20% lower dementia prevalence in IBD patients, estimated, however, with low statistical precision. 24 Finally, two recent studies from the United Kingdom 26 and Canada 25 found no overall association between IBD and dementia. The Canadian study had over 30 years of follow-up 25 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…22,23 Contrasting these studies, a Swiss cross-sectional study found an approximately 20% lower dementia prevalence in IBD patients, estimated, however, with low statistical precision. 24 Finally, two recent studies from the United Kingdom 26 and Canada 25 found no overall association between IBD and dementia. The Canadian study had over 30 years of follow-up 25 .…”
Section: Introductionmentioning
confidence: 98%
“…However, the results of studies investigating the association between IBD and dementia are conflicting. [22][23][24][25][26] A Taiwanese population-based cohort study showed a 2.5-fold increased risk of dementia in IBD patients, 22 whereas a German study of IBD patients followed in general practices found an only 1.2-fold increase. 23 Both studies had limited follow-up time and restricted age groups of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this systematic review did not include results from the United Kingdom cohort 6 where there was no significant association reported between IBD and dementia. Notably, studies from Germany 7 and Taiwan 8 found that the risk of dementia was higher in IBD patients than in the non-IBD population (HR 1.22, 95% CI 1.07-1.39 and HR 2.54, 95% CI 1.91-3.37, respectively).…”
Section: Editorial: Ibd and The Risk Of Dementia -The Jury Is Still Outmentioning
confidence: 99%
“…The present findings mirror the results of a systematic review by Liu et al 5 which concluded that a diagnosis of IBD confers an increased risk of dementia (HR = 1.27, 95% CI 1.10–1.47). Nevertheless, this systematic review did not include results from the United Kingdom cohort 6 where there was no significant association reported between IBD and dementia. Notably, studies from Germany 7 and Taiwan 8 found that the risk of dementia was higher in IBD patients than in the non‐IBD population (HR 1.22, 95% CI 1.07–1.39 and HR 2.54, 95% CI 1.91–3.37, respectively).…”
mentioning
confidence: 99%